Fixed Income Instruments to Mobilize Institutional Investors for SME Financing in EMEs - Carvajal, Ana Fiorella; Loladze, Tamuna; Hammersley, James Walter; Anderson, Jeffrey David; Walley, Simon Christopher; Kemmish, Richard (World Bank, Washington, DC, 2017)
Emerging market economies (EMEs) face significant funding gaps in strategic sectors, such as infrastructure and small and medium enterprise (SME) financing, that if not addressed can stifle growth. In this context, in 2015 the finance and markets (F and M) global practice led the production of a joint World Bank Group (WBG) and International Monetary Fund (IMF) and Organization for Economic Co-operation and Development (OECD) report for the G20 on capital markets instruments to mobilize institutional investors to infrastructure and SME financing in emerging market economies. The report focuses on fixed income instruments that can help mobilize domestic institutional investors, in particular pension funds and insurance companies, to infrastructure and SME financing in EMEs and provide policy recommendations to facilitate their use.